A 2D metal–organic framework composed of a bi-functional ligand with ultra-micropores for post-combustion CO2 capture1. Issue 59 (28th June 2015) - Xu, Guodong; Peng, Yongwu; Hu, Zhigang; Yuan, Daqiang; Donnadieu, Bruno; Zhao, Dan; Cheng, Hansong
<x xml:space="preserve">Abstract</x> A 2D MOF named NUS-5 with a unique topological structure was synthesized, demonstrating remarkable thermal stability and ultra-micropores resulting in high CO2 storage capacity and excellent sorption selectivity of CO2 over N2.